STRATEGI PENGELOLAAN TES KEMAMPUAN AKADEMIK (TKA) BERBASIS COMPUTER BASED TEST (CBT) MELALUI PENDEKATAN MANAJEMEN POAC DI SMP NEGERI 1 PASAWAHAN KABUPATEN PURWAKARTA - Cynthia Rizki Fitrianti Yahya; Fatmawati; Rahmat Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of the Academic Competency Test (TKA) through a Computer-Based Test (CBT) system represents a strategic transformation in educational assessment in Indonesia. This study aims to analyze the management strategy of TKA implementation at SMP Negeri 1 Pasawahan based on POAC. A qualitative descriptive case study was employed. Data were collected through interviews, observations, and documentation involving the principal, committee members, teachers, technicians, operators, and students. Data were analyzed using the Miles, Huberman, and Saldaña interactive model with triangulation for credibility. The findings indicate that planning included technical coordination, infrastructure mapping, scheduling, and simulations. Organizing was conducted through a structured committee with clear responsibilities. Implementation was supported by try-outs and academic reinforcement, while controlling involved cross-school supervision and evaluation. Challenges included server instability, limited facilities, internet connectivity, and students’ psychological readiness. The study concludes that systematic implementation of POAC effectively supports digital-based academic assessment management.